Development and utilization of a surrogate SARS-CoV-2 viral neutralization assay to assess mRNA vaccine responses - Wisnewski, Adam V.; Liu, Jian; Lucas, Carolina; Klein, Jon; Iwasaki, Akiko; Cantley, Linda; Fazen, Louis; Campillo Luna, Julian; Slade, Martin; Redlich, Carrie A. (PloS one, 2022)
Tests for SARS-CoV-2 immunity are needed to help assess responses to vaccination, which can be heterogeneous and may wane over time. The plaque reduction neutralization test (PRNT) is considered the gold standard for measuring serum neutralizing antibodies but requires high level biosafety, live viral cultures and days to complete. We hypothesized that competitive enzyme linked immunoassays (ELISAs) based on SARS-CoV-2 spike protein's receptor binding domain (RBD) attachment to its host receptor, the angiotensin converting enzyme 2 receptor (ACE2r), would correlate with PRNT, given the central role of RBD-ACE2r interactions in infection and published studies to date, and enable evaluation of vaccine responses. Configuration and development of a competitive ELISA with plate-bound RBD and soluble biotinylated ACE2r was accomplished using pairs of pre/post vaccine serum. When the competitive ELISA was used to evaluate N = 32 samples from COVID-19 patients previously tested by PRNT, excellent correlation in IC50 results were observed (rs = .83, p < 0.0001). When the competitive ELISA was used to evaluate N = 42 vaccinated individuals and an additional N = 13 unvaccinated recovered COVID-19 patients, significant differences in RBD-ACE2r inhibitory activity were associated with prior history of COVID-19 and type of vaccine received. In longitudinal analyses pre and up to 200 days post vaccine, surrogate neutralizing activity increased markedly after primary and booster vaccine doses, but fell substantially, up to <12% maximal levels within 6 months. A competitive ELISA based on inhibition of RBD-ACE2r attachment correlates well with PRNT, quantifies significantly higher activity among vaccine recipients with prior COVID (vs. those without), and highlights marked declines in surrogate neutralizing activity over a 6 month period post vaccination. The findings raise concern about the duration of vaccine responses and potential need for booster shots.